Mechanically durable anti-bacteria non-fluorinated superhydrophobic sponge for highly efficient and fast microplastic and oil removal. (July 2022) - Rong, Xin; Chen, Xiaoxin; Li, Pan; Zhao, Chenyang; Peng, Shan; Ma, Haiyun; Qu, Hongqiang
Abstract: Microplastics (MPs) pollution evolves into a global environmental problem to be solved urgently. Although many studies are exploring ways to remove MPs from water environment, most of them are lack of selectivity and low efficiency. Herein, considering the fascinating absorption selectivity of superwetting materials, a robust magnetic-responsive superhydrophobic and superoleophilic sponge was firstly used to quickly eliminate MPs from water with very high efficiency. The functional sponge was fabricated by a non-fluorinated coating technique that consisted of polydimethylsiloxane (PDMS) grafted Fe3 O4 particle, PDMS grafted halloysite nanotubes, and PDMS binder. The coated sponge achieved excellent mechanically durable and chemically stable superhydrophobicity that resisted a series of severe treatments. It was unquestionable to show very fast oil absorption. What's more, it especially showed very high adsorption capacity (24.3–48.2 mg/g) and could quickly adsorb almost 100% MPs (polypropylene, polyvinyl chloride, and polyethylene) from aqueous suspensions. Moreover, the removal rates remained almost 100% for these MPs after 50 cycles. Besides, the coated sponge had excellent salt tolerance and antibacterial activity to Escherichia coli ( E. coli ) (99.91%) and Staphylococcus aureus ( S. aureus ) (90.46%). The adsorption mechanism of the coating was discussed from the perspectives of molecular structure, electronic effect, steric hindrance, and size-scale effect. The absorption driving force mainly derived from the intra-particle diffusion under capillary attraction, whilst slight electrostatic interaction, hydrogen bond interaction, and σ-p (or p-p) conjugation between PDMS and MPs. This functional sponge was destined to be a new strategy in the removal of MPs and other solid pollutants, especially in the high-salinity and rich-microorganism water environment. Graphical abstract: Image 1 Highlights: A robust non-fluorinated superhydrophobic sponge was fabricated. The superhydrophobic sponge was firstly applied in MPs removal with high efficiency The sponge adsorbed almost 100% MPs (2 g/L) from aqueous suspensions within 10 min. The coated sponge exhibited excellent absorption recyclability, salt tolerance, and anti-bacteria.